2018
DOI: 10.2205/2018es000609
|View full text |Cite
|
Sign up to set email alerts
|

Study of interplanetary parameters, polar cap potential, and polar cap index during quiet event and high intensity long duration continuous AE activities (HILDCAAs)

Abstract: We observed the interplanetary datasets, polar cap potential (PCV), three different types of High Intensity Long Duration Continuous AE Activities (HILDCAAs) and polar cap index (PCI) during geomagnetically quiet period. On each event, we examine the interplanetary electric field ( ), polar cap potential (PCV), polar cap index (PCI) and westward auroral electrojet (AL) indices. We found little perturbations in during the quiet event, but significant perturbations during HILDCAAs. In particular, non-storm HILDC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…where φ represents the complex conjugate of φ and the parameters a and b are scaling and shifting factors respectively and W (a, b) gives the values of the coefficients (Adhikari et al 2017;Adhikari et al 2018).…”
Section: Wavelet Analysismentioning
confidence: 99%
“…where φ represents the complex conjugate of φ and the parameters a and b are scaling and shifting factors respectively and W (a, b) gives the values of the coefficients (Adhikari et al 2017;Adhikari et al 2018).…”
Section: Wavelet Analysismentioning
confidence: 99%
“…They reported that the RQA indicate clearly the dynamics associated with quiet intervals and HILDCAA. Adhikari et al (2018) studied the interplanetary parameters, polar cap potential, and polar cap index during geomagnetical quiet periods and HILDCAA events. Little perturbations in interplanetary electric field were found at geomagnetic quiet event, while during HILDCAA, significant perturbation was noticed.…”
mentioning
confidence: 99%